Welder Work Position Planning with the REBA Method: Rapid Entire Body Assessment - Hamzah Hamzah (Collaborate Engineering Daily Book Series, 2023)
Welding is a job with a high risk of danger for the welder, such as a hot working environment, dehydration, eye complaints, and uncomfortable working positions. One of the conditions that often occur in welding workers when carrying out work is the position of the welder's body when carrying out welding, which is required to stand. This condition will cause complaints that the welder feels because carrying out the welding process takes a long time. This causes the welder to experience pain in the legs and back and, if done continuously, will trigger long-term illness. The method used in this research is method Rapid Entire Body Assessment (REBA). From the results of manually calculating the REBA method, a score of 2 is obtained, which can be interpreted according to the REBA Classification and Risk Level as low risk. Based on the results of work posture testing on the welding section, the workload of the workers has been reduced from 5 to 2. Therefore, the best position is welding while standing with the body upright; this will help the welder work without injury and has been tested using the REBA method.